Phytochemical screening, antibacterial and free radical scavenging activity of the fruit and peel extracts of Trapa bispinosa (water chestnut) - ANJALI B THAKKAR,; SWATI K. KURTKOTI,; NANDIBATLA V.SASTRY, (International Journal of Pharma and Bio Sciences, 2018)
Trapa bispinosa, commonly known as the water chestnut, is a widely used edible plant found in Asian sub-continents and parts of Africa. The entire plant is believed to have large number of health benefits and disease fighting properties. With the rising resistance to synthetic antimicrobial agents, a need for finding newer source of medicine is increasing. The aim of the present work was to investigate the antibacterial and free radical scavenging activity of various extracts of fruit and peel of the Trapa bispinosa. Water, methanol and acetone were chosen as the solvents to carry out the extraction. Extraction was done using cold maceration technique. Preliminary investigation of phytochemicals showed the presence of major secondary plant metabolites such as alkaloids, flavonoids, glycosides, coumarins. Based on the phytochemical screening, methanol was selected as the choice of solvent as it showed greater extraction of phytochemicals. The extracts were further tested for antimicrobial and antioxidant activity. The antimicrobial activity was done against both Gram positive and Gram negative bacteria. The methanolic extract showed highest activity, almost double, against the Gram positive bacteria than the acetone and aqueous extracts. However, none of these extracts were effective against the Gram negative bacteria. Furthermore, it was observed that the antimicrobial activity of the peel extract was higher as compared to the fruit. The antioxidant activity was carried out by the Hydrogen peroxide scavenging method and it was found that the peel has more anti-oxidant activity (27.08%) compared to the fruit which showed only 18.75% activity. From the anti-microbial study and the antioxidant study, it was thus concluded that the methanolic extract of the peel of T. bispinosa is more potent antimicrobial and antioxidant agent as compared to the methanolic extract of fruit of T. bispinosa. The presence of secondary plant metabolite in the peel makes it a powerful antimicrobial against the gram positive bacteria.